ANALYSIS OF THE USE OF AFFIRMATION FIGURES IN THE OPINION RUBRIC OF THE DETIK.COM ONLINE NEWSPAPER - Dien Fitria Nur Ramadhan; Nabila; Wahyunengsih (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
The discussion raised in this study relates to the use of the figure of speech in the opinion rubric of the detik.com online newspaper. The form of the research analyzed is the use of affirmation figures of speech in the detik.com mass media. Sources of data obtained through the mass media detik.com were analyzed starting from October 2022, and the news was taken randomly every week. Data collection techniques used are analysis, observation, and documents. The results of the study were read, recorded, and explained by the use of figures of speech written in the news. The purpose of this analysis is to be able to find out what figure of speech is used in the detik.com mass media. The type of research conducted is qualitative research. The results of the study concluded that there were four types of figures of speech that the researchers found on detik.com. Among them, the repetition figurehead is found in two stories, pleonasm in one story, and anticlimactic in one news.